2019
DOI: 10.1088/1361-6501/ab198f
|View full text |Cite
|
Sign up to set email alerts
|

Vision-based adaptive stereo measurement of pins on multi-type electrical connectors

Abstract: As a non-contact inspection approach, vision technology usually undertakes the task of positioning, measuring and defect identification in the field of industrial automation. However, traditional visual programs at a high price are often designed for only a single category of products. Furthermore, the quantitative measurement tasks in the industry usually require a rigorous visual environment as well as hardware equipment, which implies a lack of generalization. Hence, it is imperative to establish a robust a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Meanwhile, compared to other existing industrial camera-based inspection > REPLACE THIS LINE WITH YOUR PAPER IDENTIFICATION NUMBER (DOUBLE-CLICK HERE TO EDIT) < 9 systems (Refs. [14][15][16] or robotic systems (Refs. 12-13), the deployed system has prominent advantages in terms of competitive price and powerful computation efficiency, as shown in Table IV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, compared to other existing industrial camera-based inspection > REPLACE THIS LINE WITH YOUR PAPER IDENTIFICATION NUMBER (DOUBLE-CLICK HERE TO EDIT) < 9 systems (Refs. [14][15][16] or robotic systems (Refs. 12-13), the deployed system has prominent advantages in terms of competitive price and powerful computation efficiency, as shown in Table IV.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the position of pins both in height and in the 2D plane where they lie, a stereo vision system [15] was designed to measure the position of pins that are present in various shapes. Then, deep neural network and pattern matching based on prior knowledge registration were introduced to a 3D vision measurement platform, which can detect abnormal positions of pins for a total of 33 types of connectors [16].…”
Section: A Fundamentals Of Acwh Inspectionmentioning
confidence: 99%
“…The results are shown in table 12. In order to validate the superiority of the algorithm proposed in this paper in terms of accuracy and detection precision, we compared it with existing literature [18,19,27] to evaluate its performance. From table 12, it can be observed that compared to the first dataset (Group x), the accuracy of the algorithm proposed in this paper has improved by 1.58%.…”
Section: Two-hole Rectangular Connectorsmentioning
confidence: 99%
“…This method of acquiring image can reduce the time for the feature extraction process such as simple segmentation and thresholding approaches are enough to determine the features of the component. Zhao et al in [312] proposed a similar stereo vision system using two cameras to inspect the pins on multi-type electrical connectors of the components. Because each film capacitor has six surfaces to be detected, Yang et al in [299] used four image acquisition systems that are adjusted to detect the surface defects of capacitors.…”
Section: B Camera/lens Selection and Positioningmentioning
confidence: 99%